Properties, performance and stability of iridium-coated water oxidation electrodes based on anodized titanium felts. Issue 2 (10th December 2020) - Hofer, André; Bochmann, Sebastian; Bachmann, Julien
Abstract : Holistic performance characterization: not only one performance parameter, but short-term electrocatalytic proficiency in process relevant conditions combined with long-term stability. Abstract : This study explores the preparation of porous titanium felts as substrates for water oxidation electrodes. We approach the characterization of their performance in a holistic manner: not just a single performance parameter is considered, but instead a combination of short-term electrocatalytic proficiency in process-relevant conditions and long-term stability. The preparation combines two ingredients: (1) anodization of the felts to generate surface porosity with (2) atomic layer deposition (ALD) to coat the porous substrates with thin iridium films of 8 nm thickness. Samples generated with anodization in various conditions are characterized quantitatively in terms of their electrochemical performance (overpotential η 10, maximum current density j max, electrochemically active surface area expressed as roughness factor rf) and of their stability (electrochemical, chemical and physical). We find that electrodes obtained by anodization in water exhibit both lower stability and lower performance than their counterparts prepared in organic electrolytes. However, the electrode type that exhibits the best pure electrochemical performance (lowest η 10 and highest j max ) also exhibits a fragile surface structure. For all samples, the very low catalyst loading on the order of tens of μg cm −2 ensures a significant materials cost reduction with respect to traditional preparative methods.